Re-evaluating the resource potential of lomas fog oasis environments for Preceramic hunter–gatherers under past ENSO modes on the south coast of Peru. (1st December 2015) - Beresford-Jones, David; Pullen, Alexander G.; Whaley, Oliver Q.; Moat, Justin; Chauca, George; Cadwallader, Lauren; Arce, Susana; Orellana, Alfonso; Alarcón, Carmela; Gorriti, Manuel; Maita, Patricia K.; Sturt, Fraser; et al.
Abstract: Lomas – ephemeral seasonal oases sustained by ocean fogs – were critical to ancient human ecology on the desert Pacific coast of Peru: one of humanity's few independent hearths of agriculture and "pristine" civilisation. The role of climate change since the Late Pleistocene in determining productivity and extent of past lomas ecosystems has been much debated. Here we reassess the resource potential of the poorly studied lomas of the south coast of Peru during the long Middle Pre-ceramic period (c. 8000–4500 BP): a period critical in the transition to agriculture, the onset of modern El Niño Southern Oscillation ('ENSO') conditions, and eustatic sea-level rise and stabilisation and beach progradation. Our method combines vegetation survey and herbarium collection with archaeological survey and excavation to make inferences about both Preceramic hunter–gatherer ecology and the changed palaeoenvironments in which it took place. Our analysis of newly discovered archaeological sites – and their resource context – show how lomas formations defined human ecology until the end of the Middle Preceramic Period, thereby corroborating recent reconstructions of ENSO history based on other data. Together, these suggest that a five millennia period of significantly colder seas on the south coast induced conditions of abundance and seasonal predictability in lomas and maritime ecosystems, that enabled Middle Preceramic hunter–gatherers to reduce mobility by settling in strategic locations at the confluence of multiple eco-zones at the river estuaries. Here the foundations of agriculture lay in a Broad Spectrum Revolution that unfolded, not through population pressure in deteriorating environments, but rather as an outcome of resource abundance . Highlights: Lomas are seasonal oases sustained by ocean fogs on the arid coast of Peru. We investigate the vegetation and archaeology of the lomas of the south coast. We show that these lomas defined human ecology during the Middle Pre-ceramic period. 5000 years of colder seas induced abundance in lomas and maritime ecosystems. This fostered a Broad Spectrum Revolution leading to sedentism and agriculture.